Priority areas for the modernization of the regional management system - Koptayeva, G.P.; Agabekova, G.N.; Berdibekova, G.S.; Chernobay, L.I. (BUKETOV BUSINESS REVIEW, 2019)
The purpose of the research in the article was to study the current state and priorities for the modernization of the regional government system. According to the results of the study, a mechanism for the modernization of regional management in Kazakhstan is presented, which should be formed in three aspects: the evolution of the functions and powers of the regional management bodies; the introduction of incentive mechanisms for managing the region; development, testing and implementation of innovative forms of territorial organization of the economy. According to the research it was found out that support of regional interests is required taking into account economic, social, environmental and other features of the territory of Kazakhstan. In this regard, the modernization of regional governance should be in line with the maximum consideration of the interests of all parties in order to provide conditions for the effective operation of economic entities in a given territory. The modernization of territorial administration should be formulated on the basis of a system aimed at the formation of a sustainable and balanced reproduction of the social, economic and natural potentials of the territory. The main condition in this case should be the positive dynamics of the characteristics of the level and quality of life of the population. Sustainability as the most important sign of territorial development is based on the long process of preserving the opportunities arising in the process of reproduction of territorial possibilities (social, natural resource, economic environment). Compliance with any regional system of certain proportions that form its potential (for example, between population size and the development of the transport network, between the development of the trading network and the area of residential zones) is a balance of territorial development.